Evaluasi Dan Perencanaan Pola Pengangkutan Sampah Kecamatan Tenayan Raya Kota Pekanbaru - Rangga Mahardika; Jecky Asmura; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Waste is the residue of human activities that form of solid waste. Waste needs to be managed to avoid having a negative impact. One effort to manage a waste is to make the transportation of waste. The purpose of this research is to evaluate the transport of waste and to make plans regarding the transport of waste in the Tenayan Raya District. Result of this research suggest that longer the distance a route takes, the greater the time it takes, it can be seen from the amount of time that SHI 73 uses to drive longest. SHI 73 have the longest route 56,3 Km. according to this there should be a change including the change of pool, route of waste transportation and shift the equipment. Pool alocation shorten avarage distance of pool to the point one of route of waste transportation from 18,8 km to 12,2 km. The changing of waste transportation route shorten avarege distance from 7,26 Km to 3,2 Km. A fence to be made at a few laystall. The vehicle that works best is armroll truck.Keywords: Waste Transportation, Waste transportation route, Waste transportation disances, Waste transportation time